ISLAM, CADAR, JILBAB DAN BURQA MENURUT PERSPEKTIF AL-QUR’AN - Raisya, Nayla; Abhirama, Muhammad Daffa (Najah Bestari, 2024)
This research aims to explain the interpretation of Islam, veil, hijab, and burqa. This research uses a qualitative approach by applying descriptive analysis method. The results and discussion of this research provide an explanation of Islam, veil, hijab, and burqa in the Qur'anic perspective. The conclusion of this research is that the use of hijab, veil, and burqa is seen as a form of protection and preservation of women's dignity in some views, although it is often controversial in some cultures. Although the hijab was known in various traditions before Islam, the concept became more prominent after the introduction of Islam, particularly in Arab societies. Debates surrounding the identification and negative judgment of the veil and burqa have also been highlighted in the context of their use in Indonesia.